A knot in the protein structure – probing the near‐infrared fluorescent protein iRFP designed from a bacterial phytochrome. (1st April 2014) - Stepanenko, Olesya V.; Bublikov, Grigory S.; Stepanenko, Olga V.; Shcherbakova, Daria M.; Verkhusha, Vladislav V.; Turoverov, Konstantin K.; Kuznetsova, Irina M.
<x xml:space="preserve">Abstract</x> The possibility of engineering near‐infrared fluorescent proteins and biosensors from bacterial phytochrome photoreceptors (BphPs) has led to substantial interest in this family of proteins. The near‐infrared fluorescent proteins have allowed non‐invasive bio‐imaging of deep tissues and whole organs in living animals. BphPs and derived near‐infrared fluorescent proteins contain a structural element, called a knot, in their polypeptide chains. The formation of knot structures in proteins was refuted for a long time. Here, we studied the denaturation and renaturation processes of the near‐infrared fluorescent probe iRFP, engineered from RpBphP2, which utilizes a heme‐derived tetrapyrrole compound biliverdin as a chromophore. iRFP contains a unique figure‐of‐eight knot. The denaturation and renaturation curves of the iRFP apoform coincided well, suggesting efficient refolding. However, the iRFP holoform exhibited irreversible unfolding and aggregation associated with the bound chromophore. The knot structure in the apoform did not prevent subsequent binding of biliverdin, resulting in the functional iRFP holoform. We suggest that the irreversibility of protein unfolding is caused by post‐translational protein modifications, such as chromophore binding, rather than the presence of the knot. These results are essential for future design of BphP‐based near‐infrared probes, and add important features to our knowledge of protein folding.